Membantu Serta Mempermudah Kader Posyandu Dalam Memanajemen Data - Indra Sayono; Ari Asyari (Jurnal Pengabdian Dian Mandala, 2023)
The benefits that can be felt from technological developments are data processing that can be done quickly, precisely, and accurately. where all data processing processes in the system can be carried out in various different places so that they can be more effective and efficient. Included in the activity report at Posyandu.